Effect of pressure on poly-l-Lactic Acid morphology. (2nd September 2016) - Baker, Christopher M.; Azagury, Aharon; Mathiowitz, Edith
Abstract: When exposed to pressures below and above its glass transition temperature (Tg ) over time, both the amorphous and crystalline regions of Poly-l -Lactic Acid (PLA) can be oriented. The most pronounced effect was the existence of an intense birefringence which lacked any sign of crystalline structure as observed by polarized light microscopy as well as the existence of a non-birefringent area in some of the same samples. Differential Scanning Calorimetry (DSC) analysis of the birefringent areas revealed decreased enthalpy of relaxation (ΔHER ) and specific heat capacity (ΔCP ) values as well as the existence of at least two Tg 's when samples were treated at 63 °C and above, indicating increased orientation of the amorphous region. These same samples additionally displayed increased crystallinity which was depicted by an increased enthalpy of crystallization (ΔH). Additionally, X-Ray Diffraction (XRD) revealed a shift from an amorphous to a crystalline structure. Regions that did not display intense birefringence revealed minimal changes in Tg, ΔHER, and ΔCP . Graphical abstract: Highlights: A method for altering the morphology of semi-crystalline PLA is proposed. The mechanism relies on the application of pressure and temperature stress over specific period of time. Amorphous orientation and increased crystallinity can be achieved under strictly controlled conditions.